The paranoid apocalypse : a hundred-year retrospective on the Protocols of the elders of Zion. - Landes, Richard, 1949-; Katz, Steven T., 1944- (Elie Wiesel Center for Judaic Studies series., 2011)
The Protocols of the Elders of Zion, first published in Russia around 1905, claimed to be the captured secret protocols from the first Zionist Congress in Basel in 1897 describing a plan by the Jewish people to achieve global domination. While the document has been proven to be fake, much of it plagiarized from satirical anti-Semitic texts, the damage was done: it had a major impact throughout Europe during the first half of the 20th century, particularly in Germany. After World War II, the text was further denounced. Anyone who referred to it as a genuine document was seen as an ignorant hate.